Antagonismo in vitro de Trichoderma spp. frente a Fusarium oxysporum Schlecht f.spcubense (E.F.Smith) Snyd. Hans - Bernal, A.=700 1 Andreu, C.M.; Moya, M.M.; Gonzalez, M.; Fernandez, O.
(Es, En)
Ilus., 8 ref.
Keywords: TRICHODERMA; FUSARIUM OXYSPORUM; ANTAGONISMO; CONTROL BIOLOGICO; BANANO; CUBA